Implantable devices for heart failure monitoring: the CardioMEMS™ system. (31st December 2019) - Volterrani, Maurizio; Spoletini, Ilaria; Angermann, Christiane; Rosano, Giuseppe; Coats, Andrew Js
Abstract: Several devices have been developed for heart failure (HF) treatment and monitoring. Among device-based monitoring tools, CardioMEMS™ has received growing research attention. This document reflects the key points of an ESC consensus meeting on implantable devices for monitoring in HF, with a particular focus on CardioMEMS™.